Teachers’ Knowledge on the Competence Evaluation of Students with Mathematical Talent - Toalongo-Guamba, Ximena (2021)
Students with mathematical talents generally receive little support to effectively guide their teaching-learning process, including assessment. This exploratory study analyzes the teachers’ knowledge about assessing these students’ mathematical competence to begin to transform this situation. A questionnaire previously validated by an expert judgment was administered to 32 in-service teachers to obtain the information; the teachers were selected through a non-probabilistic convenience sampling. The results show that there are conceptual conflicts in the use of assessment terminology by teachers and ignorance about assessing mathematical competence. Based on the information collected, some first recommendations on the evaluation of mathematical competence in general and of students with mathematical talent, in particular, are presented to contribute to the professional development of teachers.